Analysis of the Globalization of Human Capital on the Example of the Republic of Armenia - Yedigaryan, Knarik («Տնտեսագետ» հրատ․)
Human capital is a stock of health, knowledge, skills and abilities formed and accumulated through investments, which is expediently used in the labor process, contributing to an increase in labor productivity and income. As a type of capital, human capital (hereinafter referred to as HC) is quite flexible in terms of globalization. As the banking and financial system plays an important role in the movement of funds, so does the migration of the HC mobility. That is why it is important to understand the relationship between migration and HC. Developing countries (for example, the Republic of Armenia) are still lagging behind in the creation and effective use of HC, there are not enough conditions for creating a favorable environment for employees providing them with high wages, and ensuring professional growth. The latter is the main reason for the mobility of HC to move from one country to another, in order to use their own HC more efficiently. The study of the international movement of HC can be useful in the process of HC developing policies, implementing reforms in the areas of education, health care and social protection. The results of the work give an opportunity to develop a migration policy in the interests of the RA economy
Keywords: International economics